Efficacy of electro-acupuncture in postpartum with diastasis recti abdominis: A randomized controlled clinical trial - Liu, Yan; Zhu, Ying; Jiang, Liyuan; Lu, Chao; Xiao, Lijuan; Wang, Ting; Chen, Jiayu; Sun, Li; Deng, Lujun; Gu, Meiyu; Zheng, Tingting; Feng, Min; et al. (Frontiers in Public Health, 2022)
Background Electro-acupuncture (EA) has promising effects on diastasis rectus abdominis (DRA), defined as a separation of the two muscle bellies of rectus abdominis. To study, there is scant knowledge or scarce high-quality evidence. Objective We aimed to evaluate the long-term efficacy and safety of EA in treating DRA during postpartum. It was assumed that the improvement of DRA was more obvious in the EA group than in the control group. Design Randomized, controlled, blinded trial (Clinical Trial Registration: ChiCTR2100041891). Setting Hangzhou Hospital of Traditional Chinese Medicine in China. Participants Females aged 20–45 years without a past medical history of pathological rectus abdominal dissection were recruited from DRA inclusion criteria from 42 days to 1 year postpartum. Intervention 110 participants were randomly assigned in a 1:1 ratio to a control group with no EA intervention (n = 55), and EA group (n = 55). The EA group received ten sessions of EA combined with physical exercise or only physical exercise for 2 weeks with a 26-week follow-up. Measurements Outcomes were assessed at baseline, week 2, and week 26. The primary outcome was the change of the inter recti distance (IRD) and electromyographic evaluation of the pelvic floor. Secondary outcomes included elasticity of linea alba (LA), paraumbilical subcutaneous adipose tissue (SAT) measurement, body mass index (BMI), percentage body fat (F%), dyspepsia symptoms, menstrual symptoms, quality of life (QoL), pain performance of patients with lower back pain, postnatal depression symptoms (PDS), postpartum self-image, and DRA-related symptom assessment including urine leakage, frequency, and urgency, constipation, sexual dysfunction, and chronic pelvic pain. Results A total of 110 maternal (55 in each group) were recruited. The mean difference in IRD from baseline to week 2 and week 26 in all states of the two groups were reduced compared with those before treatment, with statistical significance (P < 0.05). The mean of IRD at the horizontal line of the umbilicus in the end-expiratory state was smaller in the EA group than in the control group, but the difference was not statistically significant (P > 0.05) at week 2. The mean of IRD at the horizontal line of the umbilicus in head-up and flexed knee state was smaller in the EA group than in the control group, and the difference was statistically significant (P < 0.05) at week 26. Five (9.1%) and thirteen (23.64%) adverse events were reported in EA and control groups, respectively. No serious adverse events were reported. Limitation The frequency intensity of EA parameters was selected between 4 and 6 because of individual tolerance differences. Conclusion EA is an effective approach to improve IRD, electromyographic evaluation of the pelvic floor, BMI, the elasticity of LA, paraumbilical SAT, and symptoms of DRA, with durable effects at 26 weeks. Primary funding source The Construction Fund of Medical Key Disciplines of Hangzhou (Project Number: OO20200097), Hangzhou Medical and Health Science and Technology Project No. A20200483, and Zhejiang Traditional Chinese Medicine Science and Technology Plan Project (Project Number: 2021ZQ065). Clinical trial registration http://www.chictr.org.cn/index.aspx, identifier: ChiCTR2100041891.